Building entrepreneurial universities in a specific culture—barriers and opportunities. Issue 4 (3rd July 2015) - Bhayani, Ali
<x xml:space="preserve">Abstract</x> Globally universities are facing an increasingly dynamic environment, and many have responded through becoming more entrepreneurial. European and US universities have adopted new governance structures, diversified their funding, changed their organisational structures and adopted an entrepreneurial culture to drive more innovative behaviour. Using multiple case studies, based on semi‐structured interviews, the barriers and opportunities for entrepreneurialism in five UAE universities are identified. UAE universities possess inherent qualities necessary for entrepreneurialism, including steerage, concern for economic surplus plus their performance driven environment allows quick response to the dynamic external environment; however, there are certain areas that require further development such as developing a culture of innovation, incentivising Universities to take risks as well as gaining appropriate support from the State. Based on the results of this work a change agenda has been chartered to further support and develop entrepreneurial universities in the Middle Eastern environment. Copyright © 2015 John Wiley & Sons, Ltd.